A Reconfigurable Fabric for Accelerating Large-Scale Datacenter Services (IEEE MICRO Top Pick) - Putnam, Andrew; Caulfield, Adrian; Chung, Eric; Chiou, Derek; Constantinides, Kypros; Demme, John; Esmaeilzadeh, Hadi; Fowers, Jeremy; Gopal, Gopi Prashanth; Gray, Jan; Haselman, Michael; Hauck, Scott; et al. (IEEE Micro, 2015)
To advance datacenter capabilities beyond what commodity server designs can provide, the authors designed and built a composable, reconfigurable fabric to accelerate large-scale software services. Each instantiation of the fabric consists of a 6 x 8 2D torus of high-end field-programmable gate arrays (FPGAs) embedded into a half-rack of 48 servers. The authors deployed the reconfigurable fabric in a bed of 1,632 servers and FPGAs in a production datacenter and successfully used it to accelerate the ranking portion of the Bing Web search engine by nearly a factor of two. This is the IEEE Micro's Top Picks version of the original ISCA 2014 paper.